Pembelajaran Jarak Jauh Bagi Orang Muda Katolik dalam Katekese Digital - Jesica Cindini br Sembiring; Emmeria Tarihoran (Jurnal Pendidikan Agama dan Teologi, 2024)
In this life, humans will definitely continue to learn or learn something new every day. Learning new things which are called the learning process in education. Educations is the main pillar in humans life to determine how humans develop their thinking patterns. Humans thought patterns will change and develop according to the times, taking as an example the current development of digital eras. The digital world is rapidly developing in every aspect of humans life today, long distances feel close and easy to reachs. The impact of digital developments is also felt in religious education in churches and schools. A church that lives and develops in the digital era is required to be able to follow positive currents in responding to developments in Catholic youth ministry work. This digital church ministry work includes distance or online learning in Catechesis which strives for each individual towards maturing in the Christian life. Catechesis distance learning also has challenges and opportunities which are explained in detail in this research.